2014
DOI: 10.1002/elps.201400100
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the secretome of human cancer cells: Preparation of supernatant for proteomic analysis

Abstract: Secretomic analysis requires removal of serum proteins from cell-culture media. We evaluate the proteins washed from cells prepared in bovine serum-supplemented medium. PBS and serum-free-medium (SFM) were the washing solutions. A Bradford assay was used for total protein concentration and a 1D gel and LC-MS/MS, to assign the protein to human or bovine origin. For both wash solutions, all bovine protein had been removed by the third wash, without compromising the number of living cells. Further washes reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This technique has been previously shown to induce secretion of proteins (Villarreal et al, 2013 ). Using this approach, previous work also demonstrated that short serum deprivation periods did not affect cellular viability from 48 h and inward (Del Galdo et al, 2010 ; Villarreal et al, 2013 ; Rogers et al, 2014 ). Fibroblast's supernatants were therefore collected at different confluence levels and at different collection times after serum deprivation; 24 h pre-confluence, 48 h pre-confluence, 24 h post-confluence, and 48-post confluence (please note that the term pre-confluence is defined as a confluence of 40% and post-confluence as a confluence of 95%).…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…This technique has been previously shown to induce secretion of proteins (Villarreal et al, 2013 ). Using this approach, previous work also demonstrated that short serum deprivation periods did not affect cellular viability from 48 h and inward (Del Galdo et al, 2010 ; Villarreal et al, 2013 ; Rogers et al, 2014 ). Fibroblast's supernatants were therefore collected at different confluence levels and at different collection times after serum deprivation; 24 h pre-confluence, 48 h pre-confluence, 24 h post-confluence, and 48-post confluence (please note that the term pre-confluence is defined as a confluence of 40% and post-confluence as a confluence of 95%).…”
Section: Methodsmentioning
confidence: 87%
“…The maximum recovery yield was obtained when collecting the conditioned supernatants 48 h after induction when fibroblasts were at 95% of confluence with the TCA-DOC precipitation method. Washing the cells three times with PBS before serum deprivation ruled out possible contaminants present in the bovine serum (Rogers et al, 2014 ). It cannot be excluded however that some intracellular proteins, released in the medium by cellular lysis, might be present in the collected supernatants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is known that serum deprivation can deeply affect the cellular state, in our study, according to mRNA expression levels, cells did not seem to suffer and presented a phenotype similar to that of adipocyte control. In a recent study, the impact of the washing buffers and of the number of washes were evaluated in a secretome analysis of a human cancer cell line . An important observation of this work was that washing in serum‐free medium resulted in greater lysis of the cells than washing in PBS, and that more than three washes reduced the number of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…Each 10 μL of standard BSA (0.0625, 0.125, 0.25, 0.5, 1, 1.5 and 2 mg/mL) or sample solution was mixed with 1 mL of working Bradford reagent (5× dilution of the stock Bradford solution). The mixtures were mixed well and incubated in dim light at room temperature for 10 min and the optical density at 595 nm was determined [ 17 ].…”
Section: Methodsmentioning
confidence: 99%